DINAMIKA KELOMPOK PERKUMPULAN PETANI PEMAKAI AIR DI LAHAN RAWA LEBAK - Yanti Rina D (Universitas Sebelas Maret, 2015)
Water management is the success key to successful farming in swampland. The existence of water management institutions such as the Water Users Asociation (WUA) in swampland generally has not been independent. To determine the performance of group dynamics and its relation to the level of leadership behavior of the group leader and effectiveness of WUA groups in lowland swamp, then research carried out with survey method in 2013. Sample groups are purposively determined as many as 8 units WUA group comprising: 4 (four) P3A groups in Hulu Sungai Selatan and 4 units in the district Hulu Sungai Utara on South Kalimantan Province. Samples farmers randomly selected 120 people. Primary data were collected through interviews using structured questionnaire. Data were analyzed descriptively and using Spearman's Rank correlation analysis. The results showed WUA group dynamics, leadership behavior of WUA group and effectiveness of WUA group in medium category. The good of WUA group leadership behaviors can improve group dynamics, further, the dynamic group WUA increase the effectiveness of the group. The increase in group dynamics can be done through guidance on the creation of an atmosphere conducive group, reducing the pressure groups, the development and maintenance of the group and to improve the function of the task WUA group.